Plasmon damping and charge transfer pathways in Au@MoSe2 nanostructures. (August 2021) - Abid, I.; Benzo, P.; Pécassou, B.; Jia, S.; Zhang, J.; Yuan, J.; Dory, J.B.; Gauthier Lafaye, O.; Péchou, R.; Mlayah, A.; Lou, J.
Abstract: Hybridization of plasmonic and excitonic elementary excitations provides an efficient mean of enhancing the optical absorption and emission properties of metal/semiconductor nanostructures and is a key concept for the design of novel efficient optoelectronic devices. Here we investigate the optical properties of two-dimensional MoSe2 quantum well flakes covered with Au nanoparticles supporting plasmonic resonances. Using spatially resolved confocal spectroscopy, we report the observation of a quenching phenomenon of the Raman scattering and photoluminescence emission of both the MoSe2 layer and the Au nanoparticles. We found that the quenching of the photoluminescence emission from the Au nanoparticles is partial and measurable unlike the one observed for the Au-covered MoSe2 layers, which is total. Its dependence on the thickness of the MoSe2 layer is determined experimentally. Based on electrodynamics calculations and on the electronic band alignment at the Au/MoSe2 interface, the results are interpreted in terms of (1) damping of the plasmonic resonance of the Au nanoparticles due to the optical absorption by the MoSe2 layer and (2) a two-pathways charge transfer scheme where the photoexcited electrons leak from the MoSe2 layer to the Au NPs, whereas the photoexcited holes flow in the opposite direction, that is, from the Au NPs to the MoSe2 layer. The two combined mechanisms account well for the experimental observations and complements the interpretations proposed in the literature for similar metal nanoparticles/transition metal dichalcogenide systems. Graphical abstract: Image 1 Highlights: We report on quenching of the photoluminescence of both MoSe2 sheets and Au nanoparticles after the sputtering of the Au NPs on MoSe2 . We observe and measure the dependence of photoluminescence quenching of the Au nanoparticles on the MoSe2 layer thickness The PL quenching of the Au-covered MoSe2 is interpreted as photoexcited electrons transfer from the monolayer MoSe2 to the Au NPs The plasmon damping and the leakage of holes from the Au NPs to MoSe2 led to the quenching of the PL of the Au NPs.